2023
DOI: 10.1177/10760296231161591
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Hypercoagulability in Patients with Acute Cerebral Infarction Using a Clot Waveform Analysis

Abstract: A few studies concerning hypercoagulable states have sufficiently been reported in patients with acute cerebral infarction (ACI), as ACI is generally considered to be caused by platelet activation. Clot waveform analyses (CWA) for activated partial thromboplastin time (APTT) and small amount of tissue factor FIX activation assay (sTF/FIXa) were examined in 108 patients with ACI, 61 patients without ACI, and 20 healthy volunteers. CWA-APTT and CWA-sTF/FIXa showed that the peak heights were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
6
1
Order By: Relevance
“… 26 Although clot waveform analyses for activated partial thromboplastin time (APTT) and a small amount of TF-induced clotting factor IX activation assay can detect hypercoagulability in ACI patients, routine APTT and prothrombin time cannot detect hypercoagulability. 11 Although plasma D-dimer levels are high in patients with ACI, particularly, cardioembolic ACI, they were low in patients with atherosclerotic or lacunar ACI in this study. Plasma sCLEC-2 levels were extremely high in patients with ACI, particularly, in atherosclerotic and lacuna ACI patients, suggesting that elevation of sCLEC-2 may be useful for diagnosing ACI.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“… 26 Although clot waveform analyses for activated partial thromboplastin time (APTT) and a small amount of TF-induced clotting factor IX activation assay can detect hypercoagulability in ACI patients, routine APTT and prothrombin time cannot detect hypercoagulability. 11 Although plasma D-dimer levels are high in patients with ACI, particularly, cardioembolic ACI, they were low in patients with atherosclerotic or lacunar ACI in this study. Plasma sCLEC-2 levels were extremely high in patients with ACI, particularly, in atherosclerotic and lacuna ACI patients, suggesting that elevation of sCLEC-2 may be useful for diagnosing ACI.…”
Section: Discussioncontrasting
confidence: 57%
“…Most Japanese patients with atherosclerotic ACI are generally treated with argatroban, 8 followed by those with atherosclerotic or lacunar ACI, or those with TIA, who are usually treated with aspirin or other antiplatelet agents, 1 , 7 as platelet activation may play an important role in atherosclerosis resulting in ACI or acute myocardial infarction 10 ; in contrast, patients with cardioembolic ACI should be treated with warfarin or DOACs 9 for a hypercoagulable state. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 51 , 52 reported that an increased first DPH could be a useful predictor of thrombosis. However, the increase of first DPH was not sufficient for diagnosing thrombosis in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Marked increases in the peak heights of the CWA-APTT and CWA-sTF/FIXa were also reported in patients with ACI. 52 The increase in the peak height of the CWA-APTT and CWA-sTF/FIXa is reported to be caused by a thrombin burst. 53 - 56 Although the mechanism underlying the prolonged clotting time in patients with HCC may involve hepatic dysfunction, the concomitance of both prolonged peak times and increased peak heights cannot be sufficiently understood.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulability based on CWA-APTT and sTF/FIXa has been reported in patients with acute cerebral infarction [43] and malignant neoplasms [38], which has led to the establishment of a CWA cutoff value for thrombosis. A CWA cutoff value for major bleeding is being established.…”
Section: Future Prospectives Of Cwamentioning
confidence: 99%